¿Por qué debemos respetar las garantías penales? : un enfoque consecuencialista - Larsen, Pablo (2015)
The objective of this paper is to make some contributions to the discussion of the difficulty that exists in making a balance between the efficiency in prosecuting crime and respecting the criminal law guarantees. In order to do so, and convinced that dogmatic answers like "the criminal law guarantees must be respected because they are on the Constitution and in International Human Rights Treaties" are not solid enough, I will start by showing ethical and historic factors that advise that is better to respect them, to later focus on which I consider that is the main reason: we must respect them in order to avoid some consequences that may be harmful to the rule of law. I will also analyze some arguments that hold a contrary position to the one that I sustain, in order to show what I consider that are their main inconvenient